Keikutsertaan Masyarakat dalam Kegiatan Olahraga - KS, Soegiyanto (Universitas Negeri Semarang, 2013)
Global issues related to healthy lifestyle, one of them through physical activity has become a reference for many nations and institutions continue to encourage people to actively engage in physical activity, particularly through sporting activities. Athletic institutions in Indonesia in general and Central Java and Semarang in particular also uses a global issue healthy lifestyle as a reference to develop the program and use it as a direction in a variety of activities. In many instances, the Department of Sport Science FIK Unnes have participated instrumental in promoting a healthy lifestyle, both as a driver and as a partner for other institutions. Purpose of this study was to determine the communityÃ¢â¬â¢s participation in the District Banyumanik, Gunungpati, Semarang south and Tembalang. This study used a questionnaire survey method to capture accurately the situation and condition of the public sports activities in the city of Semarang, and absorb the Ã¢â¬ÅtasteÃ¢â¬Â of society in exercising. Instruments will capture qualitative data and quantitative data. Analysis of the data used together according to the type of data obtained in order to achieve the research objectives. From the research it can be concluded: (1) Community participation in sports ÃÂ (2) Teens status as high school students, have awareness of doing exercise,and Tembalang, low, (2) Teens status as high school students, have awareness of doing exercise, (3) Teens status as a student, have a consciousness for a preliminary equipment / exercise equipment independently, (4) type of physical activity performed is the most healthy way.